Analysis of prescribing pattern of antimicrobial agents and its rationality in tertiary care rural setup of Central India - Pise, Nitin D.; Kaikade, Swapnil B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antimicrobial agents are most commonly prescribed drug and share major cost of the treatment. Excessive and inappropriate use of antimicrobial has become a global problem, resulting not only in substantial economic burden on healthcare system but also in contributing to the selective pressure favoring the emergence of antibiotic-resistant microorganisms. Antimicrobial agents which one uses for prophylactic, empiric and therapeutic purposes, depends upon the local epidemiology of infectious diseases, microbiology and resistance pattern as well as local clinical experience. Rational use of antibiotics is one of the most important way of preventing development of resistant strains to these drugs. However, for this, the health care providers should be aware of the available antibiotic prescription guidelines and should strictly adhere to it. Also, they should be updated of emerging resistant strains. Though the strict guidelines are available for the use of antibiotics, there are differences in level of knowledge and approach to antibiotic prescription among professional health care providers. Methods: The present cross sectional study was carried out in A.V.B.R. Teaching Hospital by collecting data from admitted patient’s case paper, tabulated in seven groups of diseases and different groups of antimicrobial agents prescribed. Results: Penicillin and quinolone group of antimicrobials show maximum use whereas sensitivity found more in cephalosporins and quinolone group of antimicrobials. Conclusions: It was found that Cephalosporins (3rd Gen.) are the most commonly prescribed antimicrobial agents followed by aminoglycosides (Gentamicin) and Fluroquinolones (Ciprofloxacin).